Increasing Renewable Energy Consumption Coordination With the Monthly Interprovincial Transaction Market - Cai, Ye; Liu, Ying; Tang, Xiafei; Tan, Yudong; Cao, Yijia (Frontiers in Energy Research, 2021)
The limited regulation capacity of the power grid, coupled with the imperfect market mechanism, has squeezed the space for renewable energy consumption in China. This paper proposes a renewable energy consumption mechanism through the monthly inter-provincial transactions market, to balance the revenue of each market participant and improve the consumption of renewable energy. A new player named “inter-provincial traders” is introduced to serve as the middleman for the renewable generation, users, and the power grid company. The main function of “inter-provincial traders” is to coordinate and match the user load with the output of renewable energy. In such a market mechanism, the social factors, influenced by the revenue of each trading cycle, are considered in the user responding model from the perspective of consumer psychology. Finally, a two-phase optimization model is proposed to promote renewable energy consumption coordination with the monthly inter-provincial market. The optimization model is simulated in a provincial power grid example. The results show that the model can effectively increase the consumption of renewable energy as well as improving the profit of power grid companies and users.